Оцінка успішності акліматизації, характеристика біоекологічних особливостей малопоширених плодових та ягідних видів на базі Кременецького ботанічного саду - Василюк, Олег; Євсікова, Світлана; Vasilyuk, Oleg; Yevsikova, Svetlana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті наведено результати аналізу біоекологічної структури дендрофлори. Установлено оцінку результатів успішності акліматизації на прикладі колекції малопоширених плодових і ягідних видів у Кременецькому ботанічному саду за показниками росту, генеративного розвитку та впливу екологічних факторів. The article presents the results of the analysis of biomorphological and ecological structure of dendroflora, which showed the predominance of hardy species that can be grown in conditions of moderate humidity, and the average level of ensuring of soil fertility. An estimate of the results of success of acclimatization on the example of a collection of rare fruit and berry species in Krementz Botanical garden in terms of growth, generative development and the impact of environmental factors. The results indicate that the majority of the collection are suitable for growth in soil and climatic environment that can be updated and show high frost resistance, disease resistance, invulnerability to pest. The acquired information will contribute to the creation of herbal base range of fruit and berry crops, to promote the dissemination of valuable species of plants among gardeners in our area.
Evaluation of the Success of Acclimatization, Characteristics, Biological and Ecological Characteristics of Rare Fruit and Berry Species Based on the Krementz Botanical Gardens.
Keywords: колекція; генеративний розвиток; зимостійкість; ступінь акліматизації; життєва форма; екоморфа; Collection; generative development; hardiness; degree of acclimatization; life form; ecomorph